March comes in like a lion. Volume 1 - Umino, Chica (Denpa, LLC, 2023)
"Rei Kiriyama is a seventeen-year-old professional shogi player who lives alone in Tokyo's uptown. Unfortunately, the young man lost his family at a young age, sending his life into a deep world of solitude. This is a heartfelt tale of how he recovers his life upon coming into contact with the Kawamoto sisters--Akari, Hinata, and Momo." -- Page [4] cover.